If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -6) = 5(x + 4) Reorder the terms: 4(-6 + 2x) = 5(x + 4) (-6 * 4 + 2x * 4) = 5(x + 4) (-24 + 8x) = 5(x + 4) Reorder the terms: -24 + 8x = 5(4 + x) -24 + 8x = (4 * 5 + x * 5) -24 + 8x = (20 + 5x) Solving -24 + 8x = 20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -24 + 8x + -5x = 20 + 5x + -5x Combine like terms: 8x + -5x = 3x -24 + 3x = 20 + 5x + -5x Combine like terms: 5x + -5x = 0 -24 + 3x = 20 + 0 -24 + 3x = 20 Add '24' to each side of the equation. -24 + 24 + 3x = 20 + 24 Combine like terms: -24 + 24 = 0 0 + 3x = 20 + 24 3x = 20 + 24 Combine like terms: 20 + 24 = 44 3x = 44 Divide each side by '3'. x = 14.66666667 Simplifying x = 14.66666667
| 8x=158 | | 2(x+0.5)=24 | | -45x+270=y | | 5y-2(y+2)= | | 6/10=p/4 | | 15y-45x=-30 | | -45+270=y | | 2/4=5v/5 | | -w-7=w+41 | | 12n^2-18n=0 | | 3k-5k=7k+7 | | 8/3=2/r | | m-30=-m-4 | | t/4-8=9 | | 5x^2-32x+10=0 | | n/7=5/4 | | -k=x^2-6x | | -12=6+4t | | 7(2x-2)-6(3-3x)=0 | | -x+3=x+37 | | y=-7(17/18) | | 5-3(x-9)=5(x+4) | | 5h+h-4hy+1-2h= | | 9(1/3)-(3/4)(-5) | | log(8x+3)=1 | | a+93=-a+5 | | (-25)+v=(-47) | | a/3+6=16 | | X+230=400 | | n-5=3(n+1) | | -q=7-2p | | c=2(pi)*r |